2016
DOI: 10.1007/s12560-016-9250-8
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Significance of Reovirus in Water and Wastewater

Abstract: The genus Orthoreovirus contains nonenveloped viruses with double-stranded gene segments encased in a double-layered icosahedral capsid shell. These features constitute major determinants of virion stability in the environment and virion resistance against physical and chemical agents. Reovirus (ReoV) is the general term most commonly used for all virus strains that infect humans and nonhuman animals. Several studies have demonstrated the frequent occurrence of ReoV in wastewaters and natural waters, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“… Adsorption-elution Total of 30 wastewater samples analysed, 9/30 (30%). NA ( Betancourt and Gerba, 2016 ) Calgary, Canada RV, AdV RNA extracted from a concentrated (200 µL) wastewater sample. Virus mix containing NoV GII and AdV was expected from clinical stool samples and confirmed through in-house RT-qPCR assays.…”
Section: Virus Detection Methods In Wastewater Systemsmentioning
confidence: 99%
“… Adsorption-elution Total of 30 wastewater samples analysed, 9/30 (30%). NA ( Betancourt and Gerba, 2016 ) Calgary, Canada RV, AdV RNA extracted from a concentrated (200 µL) wastewater sample. Virus mix containing NoV GII and AdV was expected from clinical stool samples and confirmed through in-house RT-qPCR assays.…”
Section: Virus Detection Methods In Wastewater Systemsmentioning
confidence: 99%
“…More recent studies conducted by Qiu et al (2015) using NanoCeram filters reported infectious reovirus as the only enteric virus detected by an integrated cell culturereal time polymerase chain reaction assay (ICC-qPCR) after chlorine disinfection and ultrafiltration of the final effluent. These studies and others (Betancourt and Gerba, 2016) suggest the relative resistance of reovirus to wastewater treatment processes compared to other enteric viruses. However, no published literature could be found on the efficiency of reovirus concentration from waters by the use of these positively charged filters.…”
mentioning
confidence: 55%
“…The potential significance of reovirus in water has generally been overlooked because of uncertainty in the nature of illness caused by this virus in humans. Reovirus appears to occur in greater or equal numbers than all enteric viruses in domestic wastewater and many surface waters; however, evidence of a plausible waterborne transmission has not been documented (Betancourt and Gerba, 2016). Aulicino et al (1996) reported the highest (100%) detection rate of reovirus in primary and secondary treated wastewater using electropositive membranes (Virosorb 1 MDS-AMF Comp., Cuno Division, Meriden, U.S.A.) and cell culture combined with virus identification by polyacrylamide gel electrophoresis (PAGE).…”
mentioning
confidence: 99%
“…Despite frequent isolation of MRV from human stool or wastewater samples 13 , 17 , 21 , this is the first report on the molecular characterisation of wastewater MRVs in Japan. Of note, the samples in this study were collected from the influent sewage of the WWTP, and it has been reported that MRVs are more sensitive to chlorine than enteroviruses during water disinfection 27 . RD cells utilised in polio surveillance are not permissive to MRV infection, whereas VeroE6 cells can be used to isolate a broad range of viruses such as severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and MRV, although there are no reports on the successful isolation of SARS-CoV-2 from wastewater.…”
Section: Discussionmentioning
confidence: 99%